Perbedaan Efektivitas Pemberian Nebulizer Dengan Menggunakan Mouthpiece Dibandingkan Dengan Masker Pada Penderita Asma Akut Di Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta - Kurnianti, Nur Rochmah, dr. Riana Sari Sp.P, dr. Endang Widhiyastuti (2015)
Background: Asthma is inflamatory disease of respiratory tract that has a low fatality rate, but there was found high incidency rate in the society. Nebulizer has already known as a supporting tool therapy by the society. It has two kinds of nebulizer there are mouthpiece and mask, which has function as suction tool. Purpose: To know the differnce of effectiveness between mouthpiece nebulizer and mask nebulizer on acute asthma patient at Balai Besar Kesehatan Paru Masyarakat Surakarta. Method: This is quasi experimental study experimental study by times series design approach. This study used 34 respondents that was diagnosed acute asthma who are in able to did APE test with maximum effort. This study used purposive sampling. Peak Flow Meter is measure instument that used in this study independent T-test were used to analize the data of this study. Result: The results of independent T-test at this study P=0,007 (P<0,05) which means there is significant. Conclution: There are difference affecieness of nebulizer between mouthpiece and mask on acute asthma at Balai Besar Kesehatan Paru Masyarakat Surakarta.